Green cleaning for dummies - Goldsmith, Elizabeth B.; Sheldon, Betsy (Hoboken, N.J. : Wiley, 2009)
More and more people are seeking more natural cleaning methods to reduce their exposure to harsh chemicals. From the kitchen and bath to the living room and laundry, this book provides readers with green solutions to every common cleaning chore. Focusing on organic, nontoxic, sustainable alternatives to conventional cleaning products, it's packed with suggestions and tips for effective cleaning, and even offers green solutions for sprucing up patios, garages, vehicles, and the exterior of a house.--From publisher description.
Includes bibliographical references (p. [257]-262) and index.
Keywords: House cleaning -- Environmental aspects; Cleaning compounds -- Environmental aspects; Natural products; Organic living